Identifying social distress: a cross-sectional survey of social outcomes 12 to 36 months after colorectal cancer diagnosis - Wright, Penny; Downing, Amy; Morris, Eva J.A.; Corner, Jessica; Richards, Mike A.; Sebag-Montefiore, David; Finan, Paul; Glaser, Adam W. (American Society of Clinical Oncology, 2015)
Purpose: To establish the prevalence and determinants of poor social outcomes after a diagnosis of colorectal cancer (CRC). Patients and Methods: All 12- to 36-month survivors of CRC (International Classification of Diseases [10th revision] codes C18 to C20) diagnosed in 2010 or 2011 and treated in the English National Health Service were identified and sent a questionnaire from their treating cancer hospital. This included the Social Difficulties Inventory, a 16-item scale of social distress (SD) comprising everyday living, money matters, and self and others subscales, plus five single items. Sociodemographic and clinical data were also collected. Analyses using descriptive statistics, 2 tests, and logistic regression models were conducted. Results: Response rate was 63.3% (21,802 of 34,467). Of the 21,802 participants, 17,830 (81.8%) completed all SD items; 2,688 (15.1%) of these 17,830 respondents were classified as experiencing SD (everyday living, 19.5%; money matters, 15.6%; self and others, 18.1%). Multivariable analysis demonstrated having three long-term conditions was the strongest predictor of SD (odds ratio [OR], 6.64; 95% CI, 5.67 to 7.77 compared with no long-term conditions), followed by unemployment (OR, 5.11; 95% CI, 4.21 to 6.20 compared with being employed), having recurrent or nontreatable disease (OR, 2.75; 95% CI, 2.49 to 3.04 compared with being in remission), and having a stoma (OR, 2.10; 95% CI, 1.86 to 2.36 compared with no stoma). Additional predictors of SD were young age (< 55 years), living in a more deprived area, nonwhite ethnicity, having advanced-stage disease, having undergone radiotherapy, and being a carer. Conclusion: Although it is reassuring a majority do not experience social difficulties, a minority reported significant SD 12 to 36 months after diagnosis of CRC. The identified clinical and social risk factors are easy to establish and should be used to target support.